Digital response and the target customer of life insurance in Ecuador - Garcés Hidalgo, Sebastián; Ortiz Abril, Cristian (mktDESCUBRE; Vol 1 No 19 (2022): Nineteenth Edition (January - June), 2022)
The general objective of this study was to identify effective communication channels to market group life insurance in Ecuador. Therefore, through the qualitative method, a bibliographic review was established according to topics such as insurance market share, ranking of insurance companies, types of insurance contracts and bibliographic review of the use of social networks in Ecuador at the population level and age. This research was developed in the months of January - March of the year 2022, it was carried out under the review of studies generated by the Instituto Nacional de Estadisticas y Censos (INEC), Federación Ecuatoriana de Empresas de Seguros, (FEDESEG), Instituto Ecuatoriano de Seguridad Social (IESS), Superintendencia de Bancos y Seguros (SBS), press releases from Ecuadorian newspapers such as El Comercio, El Universo, Ekos Negocios and Primicias magazine. As a result, it was determined that the optimal social networks to market group life insurance are Facebook and Instagram, due to their number of users and reach. Being of scientific interest the efficient digital response of Ecuadorian insurance companies that, in confinement, despite being limited in a physical channel, responded to the contracting needs generating USD 20,379,274.